Relação entre abuso de poder econômico e despesa de campanha nos municípios brasileiros (2012-2016) - Suzana Alves da Silva (2018)
What is the relation between economic power and campaign spending in Brazilian municipalities in 2012 and 2016? In order to answer this question, we hypothesize that the higher the campaign spending, the higher the probability for a candidate to be prosecuted for economic power abuse. Therefore, the main goal of this thesis is to analyze the relation between campaign finance e lawsuits for economic power abuse. The analyses use as reference the majority-based elections for mayor in all Brazilian municipalities on 2012 and 2016 elections. From a methodological perspective, this thesis uses descriptive and multivariate statistics, the latter on logistic regression. There were found evidences that confirm our main hypothesis on the positive correlation between the finance spending and a candidate seen as someone that commits economic power abuses. On average, the percentage increase of campaign spending increases the chance of a candidate being prosecuted in 1.79 percentage point. This correlation is even stronger for the incumbents, with an increase of 2.10 percentage points in the odds of being prosecuted.